A Pilot Study On The Sustainability Of The Engineers’ Technical Knowledge Repository (KR) Establishment: A Malaysian Case - Noordin, Siti Arpah Binti; Raja Mohamad, Raja Faralita Binti; Shuhidan, Shamila Mohamed (The Asian Journal of Technology Management (AJTM), 2015)
Abstract. Knowledge is an important resource in this current economic condition where organizations are competing in creating more innovation in order to maintain their business in the marketplace. Thus, it is important for an establishment to continue their capitalizing their knowledge asset as knowledge is vital to gain competitive advantage in this current epoch. With regards to that, an organization needs to plan and design the most appropriate approach which enable the organizational knowledge asset to be captured, stored and utilized its valuable benefits. Establishing a knowledge repository (KR) is one of the approaches organizations adapt in maintaining organizational knowledge asset and promoting knowledge reuse. The focal point of this research is on the sustainability of knowledge repository establishment in sharing, transferring, storing the technical knowledge of the key personnel from the Malaysian public sector. The study adopted the qualitative research approach as its aim is to look into the sustainability of KR in an in-depth manner which concerned with the societal facet of that particular system. Therefore, the paper discusses the outcomes from the pilot study on which elements that sustain the significant impact in contributing to the process of knowledge repository sustainability in an organization.Keywords: Engineers, Knowledge Repository, Knowledge Management, Malaysia, Public Sector, Sustainability, Technical Knowledge